PENGARUH IMPULSE BUYINGTERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SITUS SHOPEE: STUDI KASUS MAHASISWA STIE RAJAWALI PURWOREJO (STIE Rajawali Purworejo, 2021)
This research aims to analyze the influence of impulse buying on consumer purchasing decisions on the Shopee site (case study of STIE Rajawali Purworejo students). Data collection techniques in this research were obtained by observation, interviews, questionnaires, literature study and documentation. The population in this study were students majoring in management and accounting class 2016/2017 and 2017/2018 STIE Rajawali Purworejo, totaling 34 and the sampling technique used in this research was the census method or saturated sampling. A total of 34 people were students of STIE Rajawali Purworejo majoring in management and accounting class 2016/2017 and 2017/2018. The data analysis technique used in this research is a Likert scale to measure respondents' opinions and test instruments that were prepared. The test instruments used are: simple linear regression, coefficient of determination and partial testing (T). The simple regression analysis test shows that there is a significant influence in a positive direction between impulse buying and purchasing decisions of 0.594, meaning that if the impulse buying variable increases by one unit then will be followed by an increase in purchasing decision variables. The coefficient of determination test shows an R2 value of 0.905, meaning that 90.5% of the purchasing decision variable can be explained by the impulse buying variable. The remaining 9.5% of purchasing decisions can be explained by other variables not proposed in this research. The results of the t test showed that the t count was 17,453, which was greater than the t table (17,453 > 2.0369) and at a significant level (0.000 < 0.05), so Ho was rejected and Ha was accepted, which means that there was a positive and significant influence between the impulse buying variable on consumer purchasing decisions.